`int_-10^10 (2e^x)/(sinhx + coshx) dx`

`int_-10^10 ((2e^x)(sinhx-coshx))/(sinh^2 x- cosh^2 x) dx`

`= int_-10^10-(2e^x sinhx - 2e^x coshx) dx`

`=2 int_-10^10 -e^x sinhx + e^xcoshx dx`

`= 2 int_-10^10 e^x (e^x-e^-x)/2 + e^x (e^x + e^(-x))/2 dx`

`= 2 int_-10^10 ((e^(2x) - 1 +e^(2x) +1)/2 dx)`

`= 2 int_-10^10 e^(2x) dx...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

`int_-10^10 (2e^x)/(sinhx + coshx) dx`

`int_-10^10 ((2e^x)(sinhx-coshx))/(sinh^2 x- cosh^2 x) dx`

`= int_-10^10-(2e^x sinhx - 2e^x coshx) dx`

`=2 int_-10^10 -e^x sinhx + e^xcoshx dx`

`= 2 int_-10^10 e^x (e^x-e^-x)/2 + e^x (e^x + e^(-x))/2 dx`

`= 2 int_-10^10 ((e^(2x) - 1 +e^(2x) +1)/2 dx)`

`= 2 int_-10^10 e^(2x) dx ```

`= 2(1/2)e^(2x) = e^(2x) `

`==> e^(-20) - e^(20)`

`= 1/e^20 - e^20 `

``